EFFECTIVENESS OF USE OF COOPERATIVE LEARNING MODELS OF NUMBERED HEAD TOGETHER (NHT) TYPE AND TYPE OF THINK PAIR SHARE (TPS) ON MATHEMATICAL LEARNING OUTCOMES OF SMP MUHAMMADIYAH 1 YOGYAKARTA - Ade Prayoga; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2017)
Learning mathematics in class VII of SMP Muhammadiyah 1 Yogyakarta in the 2015/2016 academic year still uses conventional methods that result in students who are less enthusiastic about learning mathematics. The use of inappropriate learning models makes students less familiar with the material explained by the teacher and results in low mathematics learning outcomes. The population in this study were VII grade students of SMP Muhammadiyah 1 Yogyakarta which consisted of 3 classes. Samples of 2 classes with a total of 67 students were taken by random sampling technique for the class obtained VII F as the experimental class A and class VII E as the experimental class B. The research instrument was a test of learning outcomes. Data analysis uses party testing and a one-party t-test. Based on the analysis of the first hypothesis test on mathematics learning outcomes with a significant level of 5% and 65 degrees of freedom obtained by tcount= 8.12> ttable = 1,999, it shows that there are significant differences between mathematics learning outcomes using NHT type cooperative learning models and those using models TPS type of cooperative learning, and the second test with a significant level of 5% and 65 degrees of freedom obtained by tcountt= 8.12> ttable = 1.66 indicates that the cooperative learning model NHT type is more effective than the TPS cooperative learning model in improving mathematics learning outcomes students.